Biocompatible Bi(OH)3 nanoparticles with reduced photocatalytic activity as possible ultraviolet filter in sunscreens. (December 2018) - Bogusz, Kathrin; Cardillo, Dean; Tehei, Moeava; Boutard, Tifenn; Barker, Philip J.; Devers, Thierry; Rosenfeld, Anatoly; Dou, Shi X.; Liu, Hua K.; Konstantinov, Konstantin
Graphical abstract: Highlights: Facilesynthesis of inorganic Bi(OH)3 nanoparticles. High biocompatibility in human skin and dog kidney cells in vitro. Ultraviolet filter capable of reducing the photocatalytic activity of TiO2 and ZnO. Preparation of TiO2 /Bi(OH)3 and classical TiO2 /ZnO sunscreen formulations. Significantly improved photoprotection and photostability compared to TiO2 /ZnO. Abstract: In this study we investigate readily synthesised Bi(OH)3 nanoparticles as a novel, multifunctional ultraviolet filter for sunscreen. The absorbance of Bi(OH)3 NPs in the ultraviolet region is comparable to that of both ZnO and TiO2 NPs used in commercial sunscreens. In vitro photoprotection results show that the combination of TiO2 /Bi(OH)3 is more efficient than TiO2 /ZnO over the whole UV range, with an increase in sun protection factor of 28%. The emulsions show rheological properties comparable to those of commercial sunscreens. The combination of TiO2 /Bi(OH)3 led to insignificant damage on pre-painted steel panels after exterior exposure for twelve weeks. We also demonstrate that the addition of Bi(OH)3 NPs reduces the degradation of crystal violet by photocatalytically active TiO2 or ZnO NPs under ultraviolet exposure. Finally, assessment of the biocompatibility of Bi(OH)3 with HaCaT keratinocytes and Madin-Darby Canine Kidney (MDCK) cells in vitro is described.